ANALISIS HUBUNGAN ANTARA SERVICE QUALITY, CUSTOMER SATISFACTION, DAN SWITCHING COST TERHADAP CUSTOMER LOYALTY; STUDI KASUS PERPINDAHAN GSM KE CDMA MAHASISWA DI DEPOK. - Rizal Edy Halim (Universitas Trisakti, 2007)
The level of competition in the world of CDMNs telecommunications mobile in Indonesia is very tight Each CDMRs provider uses price promotion strategy to draw consumer enthusiasm. In line with the theory of price sensitivity of consumer to price changes if the consumer will move to other provider with dissimilar price offering at same service. Good service quality which can be given by service provider to its consumer will make them satisfy and loyal. Consumer which satisfied would intenl to re-purchase the services that could be generating their loyalty. If the providers offering various benefit, value, or other tactical effort to retain their customer then the level of customers switching intention will be low. Hence they will become progressively loyal and resistance to move. Using survey with a hundred of respondents, the authors found thatservice quality influence customers satisfaction positively. It means progressively improvement of service quality will boost up the level of satisfaction. The findings also addressed that customer satisfaction influence loyalty positively. Other word if customer satisfies with the sentes offering, the level of loyalty will be increase. Interestingly, the finding also shows that switching cost will disturb the chain of satisfaction toward loyalty. Here in after, this study also finds that service quality influence customer loyalty patially which means with or without the presence of satisfaction, customer have become loyal to their provider.Keywords : customer satisfaction, loyalty, switching cost